2015
DOI: 10.5901/mjss.2015.v6n5s5p216
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Financial Literacy and Household Saving among Fishermen in Indonesia

Abstract: Financial literacy literatures suggested that people in many countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
4
0
5
Order By: Relevance
“…(Yushita, 2017). This is in line with what (Hidajat, 2015) said that financial literacy does play an important role for a region or a country to foster people to understand about various financial service institutions and financial instruments that are available. Furthermore, in the third indicator, knowledge about insurance found that the informants only knew about insurance in general.…”
Section: Figure 2 Financial Literacy Farmers Must Havesupporting
confidence: 77%
“…(Yushita, 2017). This is in line with what (Hidajat, 2015) said that financial literacy does play an important role for a region or a country to foster people to understand about various financial service institutions and financial instruments that are available. Furthermore, in the third indicator, knowledge about insurance found that the informants only knew about insurance in general.…”
Section: Figure 2 Financial Literacy Farmers Must Havesupporting
confidence: 77%
“…Literasi keuangan berperan sangat penting dalam sebuah negara maupun daerah untuk membina masayarakat yang paham tentang lembaga jasa keuangan dan instrumen keuangan yang tersedia. Masyarakat yang paham tentang literasi keuangan akan berdampak terhadap kemakmurannya dan kesejahterannya (Hidajat, 2015). Faktor ini disebabkan karena masyarakat mampu mengelola keuangan secara efektif dan tepat sasaran.…”
Section: Manfaat Literasi Keuangan Bagi Masyarakat Agrarisunclassified
“…Several studies on financial literacy have been conducted to find out financial literacy relationships with financial decisions. For example, financial literacy affects investment decisions such as investing in derivatives instruments (Hsiao & Tsai, 2018), capital market (Van Rooij et al, 2011), retirement planning (Van Rooij et al, 2012;Boisclair et al, 2017), saving (Hidajat, 2015), insurance (Mahdzan & Victorian, 2013), home ownership (Gathergood & Weber, 2017) and so on, it might be assumed that: H1: Social economic characteristics influences financial literacy. H2: Financial literacy influences the investments decision through Ponzi and pyramid scheme.…”
Section: Hypothesis Developmentmentioning
confidence: 99%